(untitled) (American Journal of Pedagogical and Educational Research, 2023)
It is analyzed that the ethnographic group called "Harduri" of the residents of Guzor principality of the Bukhara Emirate in the late XIX - early XX centuries consisting of a significant part of the local population of the principality, and comments are made about this Harduri ethnographic group. The article discusses some promising information on these issues.